The Relationship between Level of Independence with Self-esteem among Older Adults in Serang Banten - Eko Natalia Sinaga, Sarma (STIKep PPNI Jawa Barat, 2024)
Aims: This research aims to see the influence of the level of independence in carrying out daily life activities on the level of self-esteem of older adults. Method: quantitative research with a cross-sectional design, sampling technique with total sampling, and a sample of 73 people. Data collection uses the Barthel Index and Rosenberg Self-Esteem guidelines via Google Forms. The research analysis is univariate to see an overview of the frequency distribution and proportions of variables. In contrast, bivariate analysis uses the Chi-Square test, which is used to determine the relationship between variables. Results: The research results show that 61.6% of older adults independently carry out daily activities, and 50.7% of older adults have high self-esteem. Moreover, there is a relationship between the level of independence in carrying out daily activities and the level of self-esteem in older adults elderly, with a p-value of 0.00. Conclusion: Older adults who are unable to carry out daily activities tend to experience low self-esteem. Therefore, nurses who provide services and assistance related to independence by optimizing the independence of older adults elderly and helping the older adults ly carry out activities that they are unable to do, as well as providing a safe environment for activities so that they can increase the older adults' elderly's self-esteem.